Under siege : portraits of civilian life in France during World War I - Young, Robert J., 1942- (Berghahn Books, 2000)
Studies on the First World War are plentiful but most tend to focus on the combatants. This volume offers a new and highly original perspective that shows the reader the civilian side of this protracted and destructive war through a succession of "snapshots": 130 excerpts from leading American and Canadian newspapers provide a collective portrait of life behind the battle lines, what is often called the "second" front. Written principally by Paris-based journalists, and intended for popular reading audiences, these articles depict ordinary people in a way that still touches the reader of today. They record eye-witness testimony of Paris under aerial bombardment, the gutted cathedrals at Reims and Arras, the cemeteries around Compiegne, the subterranean living quarters at Cambrai, and the heart-breaking orphanages at Chambly